2018
DOI: 10.1016/j.envsci.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Policy disconnect: A critical review of UK air quality policy in relation to EU and LAQM responsibilities over the last 20 years

Abstract: Air pollution is a significant global issue. In 2014, the World Health Organization (WHO) declared air pollution to be the world's largest single environmental health risk, with ambient air pollution causing 3.7 million deaths annually (WHO, 2014). The World Bank has also reported air pollution to be the fourth leading risk factor for premature deaths worldwide, resulting in 1 in 10 total deaths in 2013, at a cost to the global economy of about US$225 billion in lost labour income (World Bank and Institute for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…We argue that the design of future local air quality management should be based on the experience of existing authorities, and in that effort, the structure and practice of local air quality management in the US context must first be understood. In this effort, we ask 3 research questions: (1) what are the primary characteristics of local air quality authorities (eg, drivers, governance structures, and regulatory and non-regulatory mechanisms employed)? (2) how do practitioners of existing air quality authorities perceive the effectiveness of their programs?…”
Section: History Of Air Quality Management In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that the design of future local air quality management should be based on the experience of existing authorities, and in that effort, the structure and practice of local air quality management in the US context must first be understood. In this effort, we ask 3 research questions: (1) what are the primary characteristics of local air quality authorities (eg, drivers, governance structures, and regulatory and non-regulatory mechanisms employed)? (2) how do practitioners of existing air quality authorities perceive the effectiveness of their programs?…”
Section: History Of Air Quality Management In the United Statesmentioning
confidence: 99%
“…12 Local governments thus have the responsibility of assessing both current and future air quality based on emissions from various sources (ie, transport, industrial, and other 2 Air, Soil and Water Research significant sources), and where predictions indicate potential exceedances of national standards, the local government is required to designate Air Quality Management Areas (AQMA) and prepare air quality management plans that compliment action taken at the national level. 1,13 Although European nations have been rapidly advancing opportunities for addressing human exposure to degraded air, promulgating regulations occurs in the socio-political context of each nation, and in the case of the United States, local authorities. In the United States, effective management is hampered by a regulatory framework that manages air quality at regional and national scales.…”
Section: Introductionmentioning
confidence: 99%
“…Results from other studies point in a similar direction. For example Barnes et al (2018) identified a "policy disconnect" in the UK and argue further that a "failure of EU and national air quality policies has effectively undermined local authority action to improve local air quality" (e.g. Euro vehicle standards, lack of accountability at the local level, inconsistent EU and national requirements).…”
Section: Policy and Practice Recommendationsmentioning
confidence: 99%
“…The use of illegal defeat devices was compounded by insufficient type approval procedures on test stands and led to higher real world NO x emissions of diesel cars than expected. However, a disconnection of test stand and real-world emissions occurs even without manipulations (Barnes et al 2018;UBA 2018). In order to close this gap, new testing standards were implemented recently in the EU in terms of "realdriving emissions" (RDE) in combination with improved laboratory tests (EC 2017).…”
Section: Discourses and Outcomes In Aachenmentioning
confidence: 99%
“…With 90% of the global population breathing polluted air, poor air quality is affecting populations in rural and urban areas across the developed and developing world [1]. The UK continues to exceed the Ambient Air Quality Directive (2008/50/EC) (AAQD) annual mean limit value for nitrogen dioxide (NO 2 ) in at least thirty-seven areas of the country under the UK government's 2015 analysis of the situation [2]. Amongst these locations is Bristol, in the south west of England, a city with a population of just over 450,000 and ongoing exceedances of NO 2 [3].…”
Section: Introductionmentioning
confidence: 99%